Fcγ-Receptor-Independent Controlled Activation of CD40 Canonical Signaling by Novel Therapeutic Antibodies for Cancer Therapy - Beckmann, Karsten; Reitinger, Carmen; Yan, Xianglei; Carle, Anna; Blümle, Eva; Jurkschat, Nicole; Paulmann, Claudia; Prassl, Sandra; Kazandjian, Linda V.; Loré, Karin; Nimmerjahn, Falk; Fischer, Stephan (Antibodies, 2024)
The activation of CD40-mediated signaling in antigen-presenting cells is a promising therapeutic strategy to promote immune responses against tumors. Most agonistic anti-CD40 antibodies currently in development require the Fcγ-receptor (FcγR)-mediated crosslinking of CD40 molecules for a meaningful activation of CD40 signaling but have limitations due to dose-limiting toxicities. Here we describe the identification of CD40 antibodies which strongly stimulate antigen-presenting cells in an entirely FcγR-independent manner. These Fc-silenced anti-CD40 antibodies induce an efficient upregulation of costimulatory receptors and cytokine release by dendritic cells. Finally, the most active identified anti-CD40 antibody shows activity in humanized mice. More importantly, there are no signs of obvious toxicities. These studies thus demonstrate the potent activation of antigen-presenting cells with anti-CD40 antibodies lacking FcγR-binding activity and open the possibility for an efficacious and safe combination therapy for cancer patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: antibody; CD40; dendritic cell; immune cell activation; immunoglobulin